The Influence of SIA, Locus of Control, and Motivation on Employee Performance in Berwi Multi-Business Cooperatives - WIDNYANA, I Putu Dodi; KAWISANA, Putu Gede Wisnu Permana; NARINDRA, Anak Agung Ngurah Mayun (Journal of Social Sciences and Cultural Study, 2023)
This research aims to test and analyze the influence of Accounting Information Systems, Locus of Control and Work Motivation on Employee Performance. This research was conducted at the Multi-Business Cooperative in Mengwi District with a research sample of 95 respondents taken using a purposive sampling technique. All data obtained from the questionnaire distribution is suitable for use and is then analyzed using multiple linear regression and hypothesis testing (t-test and f-test). The research results show that the accounting information system positively affects employee performance in multi-enterprise cooperatives in Mengwi District. It shows that the better or improved the accounting information system, the greater the employee performance at the Multi-Business Cooperative in Mengwi District. Locus of control positively affects employee performance in multi-business cooperatives in Mengwi District. It shows that the better or the more locus of control there is, the greater the employee performance in the multi-business cooperative in Mengwi District. Work motivation positively affects employee performance in multi-enterprise cooperatives in Mengwi District. It shows that the better or increased work motivation, the greater the employee performance at the Multi-Enterprise Cooperative in Mengwi District.